PENGARUH KOMPOSISI MEDIA TUMBUH DAN POSISI PENANAMAN MENGGUNAKAN METODE BUD CHIP TERHADAP PERTUMBUHAN AWAL TANAMAN TEBU (Saccharum officinarum L.) VARIETAS CENNING - Nila Ayu Kristinia; Moch Darul Anwar (Jurnal Ilmiah Hijau Cendekia, 2021)
The effect of the compositionof the growing media and planting position using the method bud chip on early growth of sugarcane (Saccharum officinarum L.)Cenning variety. The purpose of this study was to determine the interaction between the composition of the growing media and the correctposition of the buds to early growth of sugarcane. This research was carried out in the Field Laboratory Faculty of Agriculture, Kadiri Islamic University, from April to June 2021. The method used in this study was a factorial randomized block design (RAKF). Results from this research is the composition of the planting medium and the position of planting gives effect on growth on plant height variables at the age of observation 30 and 50 DAT with the highest results in the M2K1 treatment. While in each single treatment composition of planting media and planting position showed the effect significantly on the variables observed number leaves, plant height and stem diameter.